PENINGKATAN KETERAMPILAN MEMBACA DAN MENULIS HURUF AL-QUR’AN MELALUI METODE QUANTUM READING QUR’ANPADA SISWA KELAS II SD NEGERI 138435 TANJUNG BALAI TAHUN PEMBELAJARAN 2017/2018 - S A L B I A H . (LP2MTBM MAKARIOZ, 2018)
This study aims to determine the increase in the ability and learning activities of students reading and writing letters of the Qur'an by applying the method of Quantum Reading Qur’andi class II SD Negeri 138435 Tanjungbalai 2017/2018 learning year. This research is a classroom action research in two cycles. The research subjects were class II students of SD Negeri 138435 Tanjungbalai in the year of 2017/2018 learning which amounted to 27 students. Data on the ability to read and write Al-Quran letters is obtained through tests while student learning activity data is obtained through observation sheets. Data is processed as described in percentage using the minimum completeness criteria reference. The results of the study show; 1) the ability of students to read and write letters of the Qur'an increases by applying the method of Quantum Reading Qur'an as indicated by an increase in the completeness of student learning outcomes in Formative I and Formative II showing an average of 77 and 82, from these data showing completion in accordance with KKM classical completeness67 % and 85% or classical completeness achieved in Cycle II, with an increase in classical completeness of 18%; 2) learning activities students read the surah al-Qur'an increases by applying the Quantum Reading Qur'an method indicated by the percentage of active students in Cycle I by 59% and in Cycle II by 85% with a 26% increase.